2020
DOI: 10.34067/kid.0002252020
|View full text |Cite
|
Sign up to set email alerts
|

Initial Validation of a Machine Learning-Derived Prognostic Test (KidneyIntelX) Integrating Biomarkers and Electronic Health Record Data To Predict Longitudinal Kidney Outcomes

Abstract: BackgroundIndividuals with type 2 diabetes (T2D) or the apolipoprotein L1 high-risk (APOL1-HR) genotypes are at increased risk of rapid kidney function decline (RKFD) and kidney failure. We hypothesized that a prognostic test using machine learning integrating blood biomarkers and longitudinal electronic health record (EHR) data would improve risk stratification.MethodsWe selected two cohorts from the Mount Sinai BioMe Biobank: T2D (n=871) and African ancestry with APOL1-HR (n=498). We measured plasma tumor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…These biomarkers have demonstrated reliable independent prognostic signals for kidney function [11,12,15,[35][36][37][38]. In our previous study, we found that including biomarkers to clinical data derived from EHR at a single-centre had better predictive performance than clinical models alone [13]. However, that study included few patients with prevalent CKD (approximately one third had CKD in the cohort with type 2 diabetes and one quarter had CKD in the APOL1 high-risk cohort).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These biomarkers have demonstrated reliable independent prognostic signals for kidney function [11,12,15,[35][36][37][38]. In our previous study, we found that including biomarkers to clinical data derived from EHR at a single-centre had better predictive performance than clinical models alone [13]. However, that study included few patients with prevalent CKD (approximately one third had CKD in the cohort with type 2 diabetes and one quarter had CKD in the APOL1 high-risk cohort).…”
Section: Discussionmentioning
confidence: 96%
“…Machine learning can combine biomarkers and EHR data to produce prognostic risk scores. We previously demonstrated that combining biomarkers and EHR data in patients with type 2 diabetes and APOL-1 highrisk genotype improved prediction of kidney outcomes over clinical models [13]. A simple risk score that improves the ability to identify patients with DKD at low, intermediate, and high risk of progressive decline in kidney function has the potential to improve outcomes through more effective use of medications and efficient resource allocation at the primary care physician level.…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan et al 32 utilized an EHR dataset to develop a random forest-based prediction model to predict incident renal failure. EHR datasets have also been used to develop traditional statistical models, including risk scores for AF.…”
Section: Discussionmentioning
confidence: 99%
“…This score is then used to stratify patients into low, intermediate, or high risk of experiencing progression over five years. This diagnostic tool, validated elsewhere, improves the ability to accurately identify patients at high risk for adverse kidney events (61% classified as high risk with KidneyIntelX compared to 40% classified as high risk with standard of care KDIGO criteria (p<0.001), allows physicians to optimize the treatment pathway with preventative measures at an earlier stage, which can slow progression to ESRD and improve patient outcomes [17,21]. The KidneyIntelX test can be integrated with EHR systems and supporting Care Navigation teams and software of health Nephrology, to proactively identify patients that meet the intended use criteria and therefore may benefit from the KidneyIntelX test (T2DM with DKD stages 1-3).…”
Section: Accepted Manuscriptmentioning
confidence: 99%